The Role of Network Quality as Moderating Variable on the Performance Enhancement of Islamic Microfinance Institutions (Cases of Baitul Mal Wat Tamwil) - Mutaqin, Muhamad; bin Mislan Cokrohadisumarto, Widiyanto (Ekonomi Syariah IAIN Kudus, 2018)
Islamic microfinance institutions (IMFI) -such as Baitul Mal Wat Tamwil (BMT)– have an important role in the development of micro-enterprises in Indonesia. Therefore, performance improvement BMT institutions should be carried out continuously in order to enhance its role in contributing to the development of the national economy, namely through the development of micro enterprises. The purpose of this study is to develop animprovement model the performance of BMT by involving the variables of human capital, Islamic business ethics, and moderation variable of network quality. Results of the study showed that the human capital and Islamic business ethics have a significant effect on the performance of BMT, and the network quality is able to strengthen the effect of human capital and Islamic business ethics in improving the performance of BMT. This result indicates that the network quality as moderation variable has an important role in improving the performance of BMT.